Brain renin-angiotensin system blockade with orally active aminopeptidase A inhibitor prevents cardiac dysfunction after myocardial infarction in mice. (February 2019) - Boitard, Solène Emmanuelle; Marc, Yannick; Keck, Mathilde; Mougenot, Nathalie; Agbulut, Onnik; Balavoine, Fabrice; Llorens-Cortes, Catherine
Abstract: Brain renin-angiotensin system (RAS) hyperactivity has been implicated in sympathetic hyperactivity and progressive left ventricular (LV) dysfunction after myocardial infarction (MI). Angiotensin III, generated by aminopeptidase A (APA), is one of the main effector peptides of the brain RAS in the control of cardiac function. We hypothesized that orally administered firibastat (previously named RB150), an APA inhibitor prodrug, would attenuate heart failure (HF) development after MI in mice, by blocking brain RAS hyperactivity. Two days after MI, adult male CD1 mice were randomized to three groups, for four to eight weeks of oral treatment with vehicle (MI + vehicle), firibastat (150 mg/kg; MI + firibastat) or the angiotensin I converting enzyme inhibitor enalapril (1 mg/kg; MI + enalapril) as a positive control. From one to four weeks post-MI, brain APA hyperactivity occurred, contributing to brain RAS hyperactivity. Firibastat treatment normalized brain APA hyperactivity, with a return to the control values measured in sham group two weeks after MI. Four and six weeks after MI, MI + firibastat mice had a significant lower LV end-diastolic pressure, LV end-systolic diameter and volume, and a higher LV ejection fraction than MI + vehicle mice. Moreover, the mRNA levels of biomarkers of HF (Myh7, Bnp and Anf) were significantly lower following firibastat treatment. For a similar infarct size, the peri-infarct area of MI + firibastat mice displayed lower levels of mRNA for Ctgf and collagen types I and III (markers of fibrosis) than MI + vehicle mice. Thus, chronic oral firibastat administration after MI in mice prevents cardiac dysfunction by normalizing brain APA hyperactivity, and attenuates cardiac hypertrophy and fibrosis.